Atrioventricular reciprocating tachycardia complicated by heart failure in pregnant women with alcohol and nicotine dependence in the 28th week of pregnancy - Стохмаль, Анна; Мілєвіч, Томаш; Банась, Томаш; Капера, Пауліна; Феніковскі, Анджей; Чайківська, Злата; Кшисєк, Юзеф (REPRODUCTIVE ENDOCRINOLOGY, 2013)
This article describes a clinical case of atrioventricular reciprocating tachycardia (AVRT) complicated by heart failure in pregnant women with alcohol and nicotine dependence in the 28th week of gestation. Atrioventricular reciprocating tachycardia was successfully cupped and pregnant performed a Caesarean section.